Fecal Microbiota Transplantation for Patients With Irritable Bowel Syndrome: A Meta-Analysis of Randomized Controlled Trials - Zhao, Hui-jun; Zhang, Xiao-jing; Zhang, Na-na; Yan, Bin; Xu, Ke-ke; Peng, Li-hua; Pan, Fei (Frontiers in Nutrition, 2022)
Background: Gut microbiota has been identified imbalance for patients with irritable bowel syndrome (IBS). Fecal Microbiota Transplantation (FMT) is a novel method to restore microbiota and treat IBS patients. Objective: To conduct a meta-analysis and estimate the efficacy and safety of FMT for the treatment of IBS patients, with subgroup analyses to explore the most effective way of FMT for IBS. Methods: All eligible studies were searched from Pubmed, Embase, Web of science and the Cochrane library through multiple search strategies. Data were extracted from studies comprising the following criteria: double-blind, randomized controlled trials (RCTs) that compared the efficacy of FMT with placebo for adult patients (≥18 years old) with IBS. A meta-analysis was performed to evaluate the summary relative risk (RR) and 95% confidence intervals (CIs). Results: Seven RCTs comprising 489 subjects were eligible for this meta-analysis. Pooled data showed no significant improvement of global IBS symptoms in patients with FMT compared with placebo (RR = 1.34; 95% CI 0.75 to 2.41, P = 0.32). A significant heterogeneity was observed among studies (I2 = 83%, P < 0.0001). There was no significant evidence of funnel plot asymmetry (Egger’s test, P = 0.719; Begg’s test, P = 1.000), indicating no existence of publication bias. Subgroup analyses revealed FMT operated by invasive routes, including gastroscope, colonoscope and nasojejunal tube, significantly improved global IBS symptoms (RR = 1.96; 95%CI 1.23 to 3.11, P = 0.004) with heterogeneity (I2 = 57%, P = 0.06) and an NNT of 3 (95%CI 2 to 14). However, FMT delivered via oral capsules showed a negative impact on patients with IBS (RR = 0.56; 95% CI 0.33 to 0.96, P =0.03) with a low heterogeneity (I2 = 39%, P = 0.2) and an NNH of 3 (95%CI 2 to 37). Conclusions: Current evidence from RCTs with all routs of FMT does not show significant global improvement in patients with IBS. However, FMT operated by invasive routes significantly improved global IBS symptoms.